Mechanical and Electrical Failure of Silver Nanowire Electrodes: A Scale Bridging In Situ Electron Microscopy Study - Schrenker, Nadine; Schweizer, Peter; Moninger, Marco; Karpstein, Nicolas; Mackovic, Mirza; Spyropoulos, Georgios; Göbelt, Manuela; Christiansen, Silke; Brabec, Christoph; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

Microscopic Deformation Modes and Impact of Network Anisotropy on the Mechanical and Electrical Performance of Five-fold Twinned Silver Nanowire Electrodes - Schrenker, Nadine; Xie, Zhuocheng; Schweizer, Peter; Moninger, Marco; Werner, Felix; Karpstein, Nicolas; Mackovic, Mirza; Spyropoulos, Georgios; Göbelt, Manuela; Christiansen, Silke H.; Brabec, Christoph; Bitzek, Erik; et al. (ACS nano, 2020)
Silver nanowire (AgNW) networks show excellent optical, electrical, and mechanical properties, which make them ideal candidates for transparent electrodes in flexible and stretchable devices. Various coating strategies and testing setups have been developed to further improve their stretchability and to evaluate their performance. Still, a comprehensive microscopic understanding of the relationship between mechanical and electrical failure is missing. In this work, the fundamental deformation modes of five-fold twinned AgNWs in anisotropic networks are studied by large-scale SEM straining tests that are directly correlated with corresponding changes in the resistance. A pronounced effect of the network anisotropy on the electrical performance is observed, which manifests itself in a one order of magnitude lower increase in resistance for networks strained perpendicular to the preferred wire orientation. Using a scale-bridging microscopy approach spanning from NW networks to single NWs to atomic-scale defects, we were able to identify three fundamental deformation modes of NWs, which together can explain this behavior: (i) correlated tensile fracture of NWs, (ii) kink formation due to compression of NWs in transverse direction, and (iii) NW bending caused by the interaction of NWs in the strained network. A key observation is the extreme deformability of AgNWs in compression. Considering HRTEM and MD simulations, this behavior can be attributed to specific defect processes in the five-fold twinned NW structure leading to the formation of NW kinks with grain boundaries combined with V-shaped surface reconstructions, both counteracting NW fracture. The detailed insights from this microscopic study can further improve fabrication and design strategies for transparent NW network electrodes.<br
Keywords: silver nanowire; five-fold twinning; transparent electrode; buckling; kinks; transmission electron microscopy; molecular dynamics